Anticausatives in transitive guise - Schäfer, Florian (Natural language and linguistic theory, 2025)
This article discusses verbs of change that allow a formally transitive construal that, nevertheless, has anticausative semantics. Verbs forming such “transitive anticausatives” (e.g., The water raised its temperature ) also form canonical anticausatives (cf. The temperature of the water rose ). Such verbs differ from verbs that only form canonical anticausatives (cf. The water warmed ) in that they do not lexicalize a fixed scale along which they measure change, so that the DP merged in the internal argument position of these verbs (a DP denoting a property concept like the temperature ) can determine the actual scale of change. When these verbs form canonical anticausatives, the entity undergoing change along this scale is realized as the possessor of this internal argument DP. When these verbs form transitive anticausatives, the entity undergoing the change is realized in the verb’s canonical external argument position, where it is, however, not assigned any external argument role. Instead, as in the canonical anticausative variant, it is interpreted as the possessor of the internal argument DP. This possessive relation is overtly reflected in English and other languages where the subject of the transitive anticausative construal binds a possessive pronoun in the internal argument DP. After an illustration of the phenomenon in typologically different languages, the article lays out the above semantic properties of the transitive anticausative construal and the verbs occurring in it. It then subsumes transitive anticausatives under the theory of the causative alternation in Alexiadou et al. ( 2006 , 2015 ) and Schäfer ( 2008 ). Particular attention is, thereby, given to the morphological marking that sets apart, in many languages, the lexical causative and the anticausative variant of (a subset of) alternating verbs (cf. English raise / rise ). Transitive anticausatives show a theoretically challenging but informative behavior here. Even though the transitive anticausative construal expresses anticausative semantics, its verb necessarily features the morphological marking that is canonically associated with its lexical causative use. This suggests that the morphological difference often found between pairs of lexical causative and anticausative verbs is only indirectly related to causative and anticausative semantics but is ultimately determined by more abstract, syntactic properties.